MAN AND LABOR: A RESEARCH IN THE HISTORY OF PHILOSOPHICAL THOUGHT (Scientific journal of the Fergana State University, 2026)
This article is a logical continuation of the research on the topic "Development of Philosophical Views on Labor", and in the second part, an analysis is made of how the concept of labor has developed based on philosophical approaches formed since the industrial revolution, in particular, capitalism and socialist thinking. The main purpose of the article is to identify, through the historical and philosophical formation and evolution of the concept of labor, how attitudes towards labor have changed at different stages and the differences that have arisen in the content and essence of labor as a result of these changes. This analysis serves as an important theoretical basis for finding solutions to labor and labor relations in the modern era.